2018
DOI: 10.1111/jnu.12453
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Physical Activity of Korean Female Adolescents in Their Peer Networks

Abstract: Purpose The purpose of this study was to examine and compare the diet and physical activity behaviors of female adolescents and their friends within classroom‐based peer networks in Korea. Design Complete social network analysis was used to examine the influence of classroom‐based peers on adolescents’ diets and physical activity. Data were collected by self‐report from 99 female adolescents in three classrooms. Methods Diet and physical activity behaviors were measured using the Adolescent Food Habit Checklis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…To our knowledge, this is the first study to assess the dietary habits of a population-based national sample of adolescents during the pandemic, using the AFHC, which is a reliable tool [ 34 ] for determining the dietary habits of different populations, including adolescents, and has been used in a number of studies [ 34 , 35 , 36 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study to assess the dietary habits of a population-based national sample of adolescents during the pandemic, using the AFHC, which is a reliable tool [ 34 ] for determining the dietary habits of different populations, including adolescents, and has been used in a number of studies [ 34 , 35 , 36 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that the AFHC score was significantly lower in adolescents who did not perform any sport (9.26) compared to those involved in some sport (10.36), and in adolescents who skipped meals (9.33) compared to those who did not skip any (10.33). Moreover, the study on dietary habits by Chung et al [ 43 ] indicated that Korean female adolescents earned an average AFHC score of 10.4. Thus, it can be emphasized that almost all the indicated AFHC scores are lower than those obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in high income countries (e.g. Korea, Italy, Australia) (Chung, Ersig, & McCarthy, 2019 ; Viggiano et al, 2015 ; Williams & Mummery, 2012 ) and in Western countries (Inchley et al, 2020 ) have similarly found that unhealthy eating behavior is a common problem among adolescents. This suggests that even in LMIC countries such as Vietnam where the fast food and similar industries are less developed and where farming remains a central part of the national identity, unhealthy diet among adolescents is a major HRB.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has shown that students' networks can influence eating behaviors, physical activity, and obesity [21]. Therefore, it seems essential to understand not only the composition and structure of these networks and identify the socially connected actors but also their influences on health behaviors that can help prevent obesity and lead to interventions related to this problem [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…After that, authors such as Cohen-Cole and Fletcher [19] added new contributions to the effects of social networks on the incidence of obesity. Other studies that discuss the relationship between obesity and social network analysis also reveal the impact of the social environment on the increase in obesity in the adolescent population [20][21][22].…”
Section: Introductionmentioning
confidence: 99%